Strabismus in children in Ibadan (1998)
5 year period, all children under the age of 16 years who presented with different forms of strabismus at the University College Hospital were collected for this study. 80% of the patients (16 patients) had esotropia, 50% of which was due to hypermetropia (8 patients) and 31 % (5 patients) was due to perinatal problems. 2 patients had ocular causes for their exotropia, a traumatic cataract and a macular soar. During the same period, a school survey was done to find out the prevalence of strabismus among school children. This was found to be 0.26% as opposed to 0.4% incidence found in the eye clinic.